Bacillus amyloliquefaciens SC06 Induced AKT-FOXO Signaling Pathway-Mediated Autophagy to Alleviate Oxidative Stress in IPEC-J2 Cells - Li Tang; Zihan Zeng; Yuanhao Zhou; Baikui Wang; Peng Zou; Qi Wang; Jiafu Ying; Fei Wang; Xiang Li; Shujie Xu; Pengwei Zhao; Weifen Li (MDPI AG, 2021)
Autophagy is a conserved proteolytic mechanism, which degrades and recycles damaged organs and proteins in cells to resist external stress. Probiotics could induce autophagy; however, its underlying molecular mechanisms remain elusive. Our previous study has found that BaSC06 could alleviate oxidative stress by inducing autophagy in rats. This research aimed to verify whether Bacillus amyloliquefaciens SC06 can induce autophagy to alleviate oxidative stress in IPEC-J2 cells, as well as explore its mechanisms. IPEC-J2 cells were first pretreated with 108 CFU/mL BaSC06, and then were induced to oxidative stress by the optimal dose of diquat. The results showed that BaSC06 significantly triggered autophagy, indicated by the up-regulation of LC3 and Beclin1 along with downregulation of p62 in IPEC-J2 cells. Further analysis revealed that BaSC06 inhibited the AKT-FOXO signaling pathway by inhibiting the expression of p-AKT and p-FOXO and inducing the expression of SIRT1, resulting in increasing the transcriptional activity of FOXO3 and gene expression of the ATG5-ATG12 complex to induce autophagy, which alleviated oxidative stress and apoptosis. Taken together, BaSC06 can induce AKT-FOXO-mediated autophagy to alleviate oxidative stress-induced apoptosis and cell damage, thus providing novel theoretical support for probiotics in the prevention and treatment of oxidative damage.